2011
DOI: 10.1371/journal.ppat.1001313
|View full text |Cite
|
Sign up to set email alerts
|

HIV Integration Targeting: A Pathway Involving Transportin-3 and the Nuclear Pore Protein RanBP2

Abstract: Genome-wide siRNA screens have identified host cell factors important for efficient HIV infection, among which are nuclear pore proteins such as RanBP2/Nup358 and the karyopherin Transportin-3/TNPO3. Analysis of the roles of these proteins in the HIV replication cycle suggested that correct trafficking through the pore may facilitate the subsequent integration step. Here we present data for coupling between these steps by demonstrating that depletion of Transportin-3 or RanBP2 altered the terminal step in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
228
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(248 citation statements)
references
References 60 publications
17
228
3
Order By: Relevance
“…If this model gains further support, one could consider a possibility where CA is displaced from PICs by the direct binding of TNPO3 to the intasome rather than CA. Recent reports have also shown that TNPO3 knockdowns reduced HIV-1 integration frequency into gene-dense regions (14). Our findings suggest that TNPO3 could directly associate with the functional nucleoprotein complex and could thus potentially affect the integration site targeting.…”
Section: Tnpo3 Does Not Interact Directly With Ca Tubes In Vitro-supporting
confidence: 66%
See 1 more Smart Citation
“…If this model gains further support, one could consider a possibility where CA is displaced from PICs by the direct binding of TNPO3 to the intasome rather than CA. Recent reports have also shown that TNPO3 knockdowns reduced HIV-1 integration frequency into gene-dense regions (14). Our findings suggest that TNPO3 could directly associate with the functional nucleoprotein complex and could thus potentially affect the integration site targeting.…”
Section: Tnpo3 Does Not Interact Directly With Ca Tubes In Vitro-supporting
confidence: 66%
“…Several candidates have been proposed including viral determinants such as IN (5), CA (6), matrix (7), and viral protein R (8) as well as the following cellular factors: importin-␣ (8), importin-␤ (9, 10), importin 7 (11), TNPO3 (12)(13)(14), Nup153, and Nup358 (10,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…S6A). (P ut vs. 100nM AZT = 9.555e-05, P ut vs. 1uM = 4.485e-07, P ut vs. 10uM = 4.384e-08, P ut vs. 2uM nev = 0.0003, P ut vs. 10uM nev = 8.572e-13, P ut vs. 100nM ral = 3.466e-11, P ut vs. 500nM ral < 2.2e-16, P ut vs. 1uM ral < 2.2e-16, P ut vs. 100nM CX = 0.0004, P ut vs. 1uM CX = 3.046e-13, P ut vs. 10uM CX = 6.122e-10, KS test Transportin-SR2 (TRN-SR2, TNPO3) is a cellular import factor of SR-rich proteins that is involved in HIV-1 entry in the nuclei of infected cells (24)(25)(26)(27)(28)(29)(30)(31). In fact, after TRN-SR2 knockdown HIV-1 nuclear entry is inhibited and, consequently, the amount of integrated DNA is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, RANBP2 aids nuclear import by at least two mechanisms: i) by "capturing" transport receptors through the FG-repeats, it conveys them towards the NPC and reduces the effective concentration of import receptors required for efficient transport, while ii) by interacting with selected cargos in a receptor-independent manner, through the RANBP2 N-ter domain, it increases the overall efficiency of nuclear import. Interestingly, RANBP2 is also implicated in the nuclear delivery and integration of certain human viruses, including Herpes simplex (Copeland et al, 2009) and immunodeficiency virus-1 (HIV-1) (Zhang et al, 2010;Ocwieja et al, 2011;). …”
Section: Ranbp2 In Interphase Nucleocytoplasmic Transportmentioning
confidence: 99%